The Effect of Cigarette Smoking on Rheumatoid Arthritis. - Raouf Rahim Mirza (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: To investigate the effect of smoking on rheumatoid arthritis as a causative factor, sero -positivity and activity. Materials and Methods: This case control study which is carried out in the rheumatology division of Suliamaniya teaching hospital and clinic from 15th August 2009 to 15th June 2010, Ninety_ two patients 73(79%) females and 19(21%) males who fulfilled the American College of Rheumatology diagnostic criteria for diagnosis of adult rheumatoid arthritis were included compared to 92 controls. Detail history of smoking taken and disease activity assessed according to DAS28j(Disease activity score of 28 joints). Results: All forty six smoker patients had active disease , 38(82.6%) had highly active disease according to DAS28j,these results are statistically significant (P-value =0.04), and 42(91.3%) of them had rheumatoid factor which means the positive relation between smoking and seropositivity also (P-value =0.000). Conclusion: Majority of smokers demonstrated highly active disease according to DAS28j measurement for disease activity , and the relation of smoking with seropositivity found to be positive. [Cukurova Med J 2014; 39(4.000): 736-742]